Association between the implementation of tobacco control policies and adolescent vaping in 44 lower‐middle, upper‐middle, and high‐income countries. (11th May 2022) - Chan, Gary C. K.; Gartner, Coral; Lim, Carmen; Sun, Tianze; Hall, Wayne; Connor, Jason; Stjepanović, Daniel; Leung, Janni
Abstract: Aim: To (i) estimate the prevalence of adolescent vaping in 47 lower‐middle, upper‐middle and high‐income countries, and (ii) test the association between implementation of World Health Organisation (WHO) tobacco control policies and adolescent e‐cigarette use (also known as vaping) in 44 countries where implementation data were available. Design: Cross‐sectional surveys. Settings: A total of 47 lower‐middle, upper‐middle and high‐income countries. Participants: A total of 151 960 adolescents (typically ages 13–15) who participated in WHO's Global Youth Tobacco Survey between 2015 and 2018. Measurements: Prevalence of past‐30‐day vaping and past 30‐day frequent vaping (≥10 days) were estimated from the surveys. Data on the implementation of six tobacco control measures including monitoring, smoke‐free policies, cessation programs, warning about the dangers of tobacco, advertising bans and taxation were taken from WHO's report on global tobacco epidemic. Findings: The overall weighted prevalence of adolescent vaping and frequent vaping in the past 30 days was 8.6% (95% CI, 8.3‐8.9) and 1.7% (95% CI, 1.6‐1.8), respectively. For five of WHO's policies (monitoring, smoking‐free environment, cessation programs, health warning and advertising bans), their association with adolescent vaping was inconclusive because of large variation of their effects across countries. Higher tax on combustible tobacco products was associated with higher adolescent vaping (> = 75% tax vs < 25% tax; odds ratio = 2.58; 95% CI, 1.25‐5.21). Conclusion: In 47 lower‐middle, upper‐middle and high‐income countries from 2015 to 2018, ~1 in 12 (8.6%) adolescents reported vaping in the past 30 days, but prevalence of frequent vaping was low (1 in 60; 1.7%). A higher tobacco tax was associated with higher adolescent vaping.